1996
DOI: 10.1104/pp.110.2.445
|View full text |Cite
|
Sign up to set email alerts
|

Envelope Membranes from Spinach Chloroplasts Are a Site of Metabolism of Fatty Acid Hydroperoxides

Abstract: Enzymes in envelope membranes from spinach (Spinacia oleracea 1.) chloroplasts were found to catalyze the rapid breakdown of fatty acid hydroperoxides. In contrast, no such activities were detected in the stroma or in thylakoids. In preparations of envelope membranes, I)S-hydroperoxy-10(0,1 2(Z)-octadecadienoic acid, 13s-hydroperoxy-g(Z),ll(€)-octadecadienoic acid, or 13s-hydroperoxy-9(Z),11 (0,15(Z)-octadecatrienoic acid were transformed at almost the same rates (1-2 p n o l min-' mg-' protein). The products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(106 citation statements)
references
References 37 publications
9
95
0
2
Order By: Relevance
“…The key role of chloroplast lipids in synthesis of products derived from fatty acid hydroperoxides, the so-called oxylipin pathway, was first established using mutants of PUFA synthesis for freezing-induced volatile aldehyde production (54). Furthermore, the metabolism site of fatty acid hydroperoxides was shown to be located on the envelope membranes of chloroplasts (55), and it appeared that some pathogen-or MeJA-induced LOX genes are chloroplasttargeted (49,56). In addition, morphological changes on chloroplasts were previously observed in various models of plantpathogen interaction (6 -8) and in cryptogein-treated tobacco leaves (57).…”
Section: Discussionmentioning
confidence: 93%
“…The key role of chloroplast lipids in synthesis of products derived from fatty acid hydroperoxides, the so-called oxylipin pathway, was first established using mutants of PUFA synthesis for freezing-induced volatile aldehyde production (54). Furthermore, the metabolism site of fatty acid hydroperoxides was shown to be located on the envelope membranes of chloroplasts (55), and it appeared that some pathogen-or MeJA-induced LOX genes are chloroplasttargeted (49,56). In addition, morphological changes on chloroplasts were previously observed in various models of plantpathogen interaction (6 -8) and in cryptogein-treated tobacco leaves (57).…”
Section: Discussionmentioning
confidence: 93%
“…2), and this likely applies to potato LOXZ and LOX3. Isoforms of several enzymes of this pathway have been detected in leaf plastids (Douillard and Bergeron, 1981;Vick and Zimmerman, 1987;Song et al, 1993;Feussner et al, 1995;Harms et al, 1995;Blée and Joyard, 1996). Bell et al (1995) showed that the expression of AtLox2 is required for wound-induced JA accumulation in Arabidopsis, and Harms et al (1995) showed that a constitutive increase in JA resulted from the expression of a flax allene oxide synthase in transgenic potato plants (Harms et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The oxylipins were extracted as described above and analysis was performed with an Agilent 1100 HPLC system coupled with a Raytest Ramona detector [16]. Substrates and products were separated by reversed phase chromatography according to [17]. For detection of reaction products the absorbance at 252 nm and the radioactive signal were recorded.…”
Section: Determination Of I N Vivo Activity and Metabolic Profiling Omentioning
confidence: 99%